2019
DOI: 10.4315/0362-028x.jfp-18-323
|View full text |Cite
|
Sign up to set email alerts
|

Older Adults and Parents of Young Children Have Different Handling Practices for Raw Poultry

Abstract: Salmonella and Campylobacter are among the most common causes of foodborne disease in the United States. Most illnesses are associated with eating raw or undercooked poultry or cross-contamination. Young children and older adults are more susceptible to contracting foodborne illness and have serious infections compared with other age groups. We conducted a Web-based survey of parents of young children (n = 1,957) and older adults (n = 1,980) to estimate adherence to recommended food safety practices for raw po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 32 publications
3
10
0
Order By: Relevance
“…With the exception of poultry-washing, the risky food-handling behaviors expressed by focus group participants were consistent with those reported as part of more recent research and included behaviors such as a failure to use a cooking thermometer or the consumption of undercooked eggs [ 18 , 19 , 21 , 39 ]. Previous quantitative surveys of both older and younger consumers reported that approximately 70% of them wash raw poultry at least some of the time [ 21 , 41 , 42 ]. Only about one-third of focus-group participants reported washing raw poultry.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…With the exception of poultry-washing, the risky food-handling behaviors expressed by focus group participants were consistent with those reported as part of more recent research and included behaviors such as a failure to use a cooking thermometer or the consumption of undercooked eggs [ 18 , 19 , 21 , 39 ]. Previous quantitative surveys of both older and younger consumers reported that approximately 70% of them wash raw poultry at least some of the time [ 21 , 41 , 42 ]. Only about one-third of focus-group participants reported washing raw poultry.…”
Section: Discussionsupporting
confidence: 60%
“…It was previously recognized that older adults were more observant of food safety recommendations when compared to younger age groups [ 22 , 23 ]; however, the results of more recent research suggest that, regardless of whether they are more or less adherent to the recommendations than younger consumers, older adults engage in numerous unsafe food-handling practices [ 18 , 19 , 20 , 21 , 39 , 40 , 41 ]. With the exception of poultry-washing, the risky food-handling behaviors expressed by focus group participants were consistent with those reported as part of more recent research and included behaviors such as a failure to use a cooking thermometer or the consumption of undercooked eggs [ 18 , 19 , 21 , 39 ]. Previous quantitative surveys of both older and younger consumers reported that approximately 70% of them wash raw poultry at least some of the time [ 21 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, 2020; Cardoso et al , 2021), and have a strong desire to clean the surface of the chicken from any slime, liquid or debris, which is consistent with previous research (Vatral and Quinlan, 2021). Kosa et al. (2019) identified twenty key food safety behaviors including practices to avoid cross-contamination, using a food thermometer, and discarding raw poultry beyond the safe useable timeframe.…”
Section: Discussionmentioning
confidence: 99%
“…London NHS Region had a greater hazard of AGE than other parts of the country HR hazard ratio, CI confidence interval, IMD index of multiple deprivation 40]. However, reports from recent surveys suggest there are variable rates of uptake [41,42].…”
Section: Comparison With the Literaturementioning
confidence: 99%